2022
DOI: 10.4103/jmas.jmas_129_22
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of ‘enhanced-view totally extra-peritoneal’ (eTEP) approach for ventral hernia: Early results

Abstract: Introduction: Laparoscopic ventral hernia repair is undergoing a paradigm shift with the introduction of numerous new techniques to improve the outcomes. Enhanced-view totally extra-peritoneal (eTEP) is a novel approach for the repair of ventral herniae introduced by Belyansky et al. The key innovation lies in placing the mesh in a large retrorectus–pre-peritoneal space contrary to the widely practiced intra-peritoneal placement. This approach can be easily coupled with a component separation in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…16 A 3-year (2018-2021) single-center experience from India with a total of 150 patients showed a mean operative time of 124.3 ± 23.6 and 222.2 ± 32.5 min, respectively. 17 The longer operative time is one drawback of the eTEP procedure. This also reflects our learning curve, which can be improved over time with experience and further standardization of our technique.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…16 A 3-year (2018-2021) single-center experience from India with a total of 150 patients showed a mean operative time of 124.3 ± 23.6 and 222.2 ± 32.5 min, respectively. 17 The longer operative time is one drawback of the eTEP procedure. This also reflects our learning curve, which can be improved over time with experience and further standardization of our technique.…”
Section: Discussionmentioning
confidence: 99%
“…Other reported SSOs include (1) dehiscence of the plicated linea alba/anterior fascia resulting in upper abdominal bulging and (2) disruption of the PRS/peritoneum resulting in bowel herniation and/or obstruction. 8,17,25,26 The first randomized controlled trial (RCT) in 2022 comparing eTEP (30) and IPOM (30) for ventral hernia showed that the former was more cost-effective and associated with lower seroma rates, postoperative pain scores, and earlier return to activity. 27 In 2023, another RCT (29 eTEP vs. 27 IPOM) also showed lower postoperative pain scores with eTEP but was associated with higher surgeons' workload.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations